Evaluation of almond cultivar adaptation in Trás-os-Montes region (Portugal) - Cordeiro V.; Alves C.; Vieira J.; Barroso M.R. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
- In the nineties some new almond cultivars were introduced in Portugal but their characteristics were only described in the literature. In 1998 a field trial was established at 'Centro Experimental da Terra Quente' (Quinta do Valongo, Trás-os-Montes) using some of the introduced cultivars: 'Francolí', 'Masbovera', 'Glorieta', 'Lauranne' and 'Ferragnès', grafted on GF-677 rootstock. The goals of this work were: To evaluate the behaviour of foreign cultivars in comparison with 'Ferragnès', grown in Trás-os-Montes region; to determine the relative bloom and harvest dates; and to evaluate the kernel characteristics of the new cultivars. The results obtained from data collected in 2002 indicated that 'Lauranne' was the most productive with 5 kg nuts per plant. Regarding vigour, recorded by measuring trunk diameter 20 cm above ground level, 'Francolí' was the most vigorous, with 81 mm. No differences were found for the blooming time among cultivars, except for 'Lauranne' that flowers 4 days after the others.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)